Dreamweaver 4 for Windows and Macintosh - Towers, J. Tarin. 4 0 16; 5 (Berkeley, CA : Peachpit Press, 2001)
A visual guide to the Web design software Dreamweaver that contains screen captures, step-by-step instructions, and tips, covering everything from learning Dreamweaver tools to sharing files.
Includes index.;Cover title: Macromedia Dreamweaver 4 for Windows & Macintosh.
Adult;Adult.
Keywords: 2 -- 0; 6; Dreamweaver (Computer file);Dreamweaver (Computer file); Authoring programs. -- Web sites;Web publishing.;Dreamweaver (Computer file).; 20; 2